New Member of Editorial Board - Vitchev, Grazyna Rembielak (Serbian Journal of Management, 2012)
Dr. Grazyna Rembielak-VitchevSenior Lecturer in Marketing, Director of School and College Liaison, Widening Participation Champion,  Salford Business SchoolBA(Hons) BSc(Hons) MA MSc PhD